ANALISA KAWASAN RAWAN BANJIR DI KABUPATEN KAMPAR MENGGUNAKAN APLIKASI SISTEM INFORMASI GEOGRAFIS - Nurdin; Fakhri Fakhri (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2020)
Kampar District is traversed by two large rivers and several small rivers, including Kampar River which is ± 413.5 km long with an average depth of 7.7 m, and an average width of 143 m. Referring to Central Statistics Agency Kampar Regency (2015), Kampar residents numbered 703,005 people with a growth of 2.57% that exceeded the national population growth in 2010 of 1.49%. The Kampar Kanan River has a much larger flood impact than Kampar Kiri River because the majority of the population lives along the banks of the Kampar Kanan River. Areas that are always targeted need to be mapped in the form of flood vulnerability maps within Kampar regency. To map areas susceptible to flooding in Kampar District can be done using remote sensing data based on Geographic Information System (GIS). Analysis of the overlay map results as an indicator of flooding in 4 flood vulnerability classes in Kampar regency. Overlaid maps consist of Rainfall Map, Slope Map, Land Use Map and Geological Map, which resulted in the widest area in Kampar District in the prone category of 459,977.89 ha or 42.86% of the district area. The second sequence is in the non-vulnerable category 236,082.39 ha or 22.00%. While the order of the 3rd area is in very vulnerable category that is 219.279.54 ha or 20.43%, and the smallest area is in the safe category of 157,835.01 ha or 14.71% of Kampar Regency area.